The Effect of the Age of the First Egg-Laying on the Egg Production, Hatchability and Egg Quality of Pheasants (Phasianus colchicus) - Ozbey, Orhan; Esen, Fikret; Aysondu, Mehmet Hanifi (Medwell Online, 2011)
The aim of this study was to determine the effect of the age of the first egg laying on the egg production, hatchability and egg quality of pheasant. Seventy two female ring-necked pheasants of the same age and breed under identical circumstances were included in the study. The individual egg production was recorded daily until 53 weeks of age and four groups were formed using the age for the first egg-laying (<34, 35-36, 37-38, >39 weeks). The parameters investigated in this study included egg production, egg weight, hatchability of total eggs, fertility, hatchability of fertile eggs, shape index, shell weight, shell thickness, yolk weight, albumen weight, yolk index, albumen index and the haugh unit of the groups. There was a significant difference between the groups in terms of egg production and egg weight (p<0.05). The difference between the groups for the hatchability of total eggs, fertility and hatchability of fertile eggs was also significant (p<0.05). In addition, the differences between the groups for shape index, shell weight and index, yolk weight and index, albumen weight and index and Haugh unit were significant (p<0.05). It was concluded that a selection program including those with earlier possible age for the first egg-laying in pheasants would be convenient for the egg production whereas a selection including the ones with older ages for the first egg-laying would be convenient for the egg weight, hatching and egg quality.
Keywords: Pheasant; first laying egg age; egg production; hatching characteristics; egg quality; Turkey